Influência do acabamento superficial na sobrevivência em fadiga de coroas de dissilicato de lítio - Rocha, Larissa Simião da (2020)
The objective of this study is to analyze the influence of the surface finish on the fatigue behavior and on the failure mode of restorations made with lithium disilicate glass-ceramic. Crowns of lithium disilicate glass-ceramics were made in the shape of the second upper premolar (N = 60), which were cemented in material analog to dentin. Cemented crowns were divided into two randomized groups: GD: wear with diamond bur; GP: wear with diamond bur, finishing and polishing with rubber burs and diamond paste. Wear and polishing were performed on the mesial shredding strands of the buccal and palatal cusps and center of the marginal crown crest. Afterwards, these were tested in cyclic fatigue using anatomical pistons, simulating dental trypoidism, a load of 100N at 2Hz was applied for 1x106, 2x106 and 3x106 cycles. The crowns were analyzed using transillumination, optical microscopy and scanning electron microscope. The presence of crack, chipping or catastrophic fracture after each lifetime was considered a failure. There was no statistically significant difference between the groups (p=0.741). In the polishing group, there was a predominance of crack-type fractures. Only one catastrophic fracture was observed in the finishing group. The highest frequency of failures was observed in the smallest number of cycles. Fatigue promoted surface damage that caused cracks, chipping and catastrophic fracture. The extent of the fracture may be related to defects generated by surface finishes.